2017
DOI: 10.1016/j.jaip.2017.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Control and Sputum Eosinophils: A Longitudinal Study in Daily Practice

Abstract: At the individual level, asthma control was associated with fluctuations in sputum eosinophil count over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…A retrospective study on a large asthma cohort has shown that patients combining sputum eosinophil >3% and blood eosinophil counts >400/lL have poor asthma control and are prone to exacerbate. 58 Sputum induction can be effectively performed in adults, but there might be difficulty in collecting sufficient sputum in children under 8 years. 57 Furthermore, in a large retrospective cohort of asthmatics, it has been shown that both fluctuation in FEV1 and fluctuation in sputum in sputum eosinophils independently correlated with change n ACQ6.…”
Section: Sputum and Bronchoalveolar Lavagementioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study on a large asthma cohort has shown that patients combining sputum eosinophil >3% and blood eosinophil counts >400/lL have poor asthma control and are prone to exacerbate. 58 Sputum induction can be effectively performed in adults, but there might be difficulty in collecting sufficient sputum in children under 8 years. 57 Furthermore, in a large retrospective cohort of asthmatics, it has been shown that both fluctuation in FEV1 and fluctuation in sputum in sputum eosinophils independently correlated with change n ACQ6.…”
Section: Sputum and Bronchoalveolar Lavagementioning
confidence: 99%
“…57 Furthermore, in a large retrospective cohort of asthmatics, it has been shown that both fluctuation in FEV1 and fluctuation in sputum in sputum eosinophils independently correlated with change n ACQ6. 58 Sputum induction can be effectively performed in adults, but there might be difficulty in collecting sufficient sputum in children under 8 years. 51,56 Furthermore, one study in children using sputum eosinophils for monitoring asthma was negative.…”
Section: Sputum and Bronchoalveolar Lavagementioning
confidence: 99%
“…There is substantial heterogeneity in the presentation of severe asthma and several distinct severe asthma phenotypes have been identified (1,2). One of these is severe eosinophilic asthma, characterized by poor asthma control, eosinophilic inflammation, frequent exacerbations and reduced lung function (1,2,(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore worth noting that one‐third of uncontrolled asthmatics despite treatment with high‐dose ICS at baseline were successfully weaned off ICS without any clinical degradation. Besides, monitoring sputum eosinophils during the step‐down process is of importance because some patients may tolerate an increase in sputum eosinophils without any degradation in asthma control, as previously reported . In those patients, the ICS dose should be raised to reduce the risk of exacerbations associated with eosinophilic inflammation …”
Section: Discussionmentioning
confidence: 98%
“…Fractional exhaled nitric oxide (FENO) was measured at a flow rate of 50 mL/s (NIOX; Aerocrine, Solna, Sweden). Sputum induction and processing with the whole‐sample technique was performed as previously described . The technician who performed the sputum cell count was blind to the clinical status of patients.…”
Section: Methodsmentioning
confidence: 99%